PENGARUH LIFESTYLE DAN TECHNOLOGY ACCEPTANCE MODEL TERHADAP WISATAWAN PENGGUNA TRAVELOKA PAYLATER - Sahrul Mahardiansyah, Mochammad; Kusuma Negara, I Made; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p17, 2024)
The majority of aspects in life have transformed from traditional to digital technology utilization. E-Wallets enable payment transactions, such as pay-later services, cryptocurrencies, etc., resulting in efficiency. Traveloka, for instance, launched the pay-later payment service. This research aimed to analyze and understand the influence of lifestyle and the Technology Acceptance Model (TAM) on the purchase decision of Traveloka pay-later flight ticket products. This study collected 100 samples selected through purposive sampling technique, consisting of millennial tourists who used Traveloka pay-later for purchasing flight tickets to Bali. Data collection techniques included observation, questionnaire distribution, interview, and documentation study. Data analysis was conducted using a descriptive quantitative approach to explain the relationship between lifestyle, TAM, and the purchase decision, utilizing SPSS version 29. The research concluded that the lifestyle variable () has a significant partial effect with a significance value of 0.027. The TAM variable () has a significant partial effect with a significance value of <.001. Moreover, both lifestyle () and TAM () have a positive and significant simultaneous effect with a significance value of <.001. Based on the coefficient of determination analysis, lifestyle () and TAM () explain approximately 63% of the variance in the purchase decision variable.